An innovative survey poles configuration: an alternative 3-D volume calibrating system - Rambely, A.S.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Usman, J.; Yusof, M.S. (2003)
The purpose of this study is to develop an alternative method for calibrating a threedimensional volume. The new calibration frame uses a set of four poles, consisting of 20 control points. An experiment was conducted to compare the result obtained using two methods of calibration, the Peak calibration frame (the control) and the ISN-UM survey poles system (the new reference frame). It was found that the results obtained from the ISN-UM calibration frame are comparable to those obtained using the Peak calibration frame, despite the differences in the locations and the numbers of control points, as well as the physical characteristics of both structures.